Unravelling the Markups Changes The Role of Price Elasticity of Demand and Concentration - Gradzewicz, Michał; Mućk, Jakub (Central European Journal of Economic Modelling and Econometrics, 2024)
We propose a framework identifying sources of markup changes. Our approach derives from the conjectural variation theory and highlights the role of both price elasticity and concentration in shaping the markups. We show that a decline in markups in Poland, showed by by Gradzewicz and Mućk (2024), is related to rising price elasticity of demand, while rising concentration mitigated this effect. Moreover, we document that the globalization trends, e.g. international fragmentation, increasing standardization and tighter integration with global economy, affect both price elasticity of demand and markups. We also identify factors specific to demand elasticity (product varieties and a home bias) and to markups (import content of exports).